2022
DOI: 10.1098/rsob.210361
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CRISPR/Cas9-mediated gene disruption in the tetraploid protist Giardia intestinalis

Abstract: CRISPR/Cas9-mediated genome editing has become an extremely powerful technique used to modify gene expression in many organisms, including parasitic protists. Giardia intestinalis , a protist parasite that infects approximately 280 million people around the world each year, has been eluding the use of CRISPR/Cas9 to generate knockout cell lines due to its tetraploid genome. In this work, we show the ability of the in vitro assembled CRISPR/Cas9 components to succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
(107 reference statements)
1
10
0
Order By: Relevance
“…The development of drug markers other than neomycin, puromycin, and blasticidin will accelerate research on the improvement of genetic technology in Giardia . The knockout methodology recently reported by Horáčková et al [ 27 ] was fundamentally similar as we did. However, they suggested that their method was a highly efficient process for removing non-essential genes ( mem , cwp1 , and mlf1 ) in a one-step process and used fluorescence in situ hybridization to identify a deletion mutant.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The development of drug markers other than neomycin, puromycin, and blasticidin will accelerate research on the improvement of genetic technology in Giardia . The knockout methodology recently reported by Horáčková et al [ 27 ] was fundamentally similar as we did. However, they suggested that their method was a highly efficient process for removing non-essential genes ( mem , cwp1 , and mlf1 ) in a one-step process and used fluorescence in situ hybridization to identify a deletion mutant.…”
Section: Discussionsupporting
confidence: 53%
“…The CRISPR system using nuclease-dead Cas9, instead of Cas9, was developed and successfully knocked down the expression of motor proteins, kinesin-2a and kinesin-13, and a ventral disc protein [ 26 ]. Recently, Horáčková et al [ 27 ] attempted genome editing using an in vitro assembled CRISPR/Cas9 component, but they had no success. Instead, they made a knockout mutant of three genes [ mem (multiple high cysteine membrane), cwp1 and mlf1 ] using a Cas9-expressing cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Having established the integration of Gi BolA within the mitosomal late ISC pathway, we next examined the role of BolA in the formation of Fe-S clusters. To this aim, using the recently established CRISPR/Cas9-mediated gene knockout approach (60) and a G. intestinalis cell line lacking bolA gene (ΔbolA) was generated (Fig. 4B, 4C).…”
Section: Resultsmentioning
confidence: 99%
“…For CRISPR/Cas9-mediated knockout of bolA gene, gRNA sequence ATCAGCTCTCCCGACTTCAA was inserted into gRNA cassette of pTGuide vector using (60) two annealed oligonucleotides (see Supplementary Table 5 for primers and restriction enzymes used). The 999 bp of 5’ and 940 bp 3’ homologous arms surrounding bolA gene were inserted into pTGuide vector as the homologous arms for the recombination of the resistance cassette (Supplementary Table 5).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the newly introduced G . intestinalis adapted CRISPR/Cas9 method will make it possible to efficiently create gene knockouts in the parasite [ 78 ], as well as in the IECs [ 79 ]. The combination of genetically modified G .…”
Section: Discussionmentioning
confidence: 99%